Developing critical thinking of children while teaching foreign languages using digital technologies - Majodova Gulruh Kamaridinovna (Genius Journals, 2023)
As technology continues to play an increasingly vital role in our daily lives, it is essential to incorporate it into our educational systems to facilitate the development of essential skills, such as critical thinking in children. The English language is a crucial component of a child's education, and digital technologies can provide an effective means of developing critical thinking skills during English classes. In this article, we will explore the significance of critical thinking, discuss the challenges that arise when developing critical thinking skills in children, and explore how digital technologies can be leveraged to address these challenges
Keywords: Critical Thinking; conservative educational ideology; the soft liberal position; critical and feminist pedagogy